Fatal strike [large type] - Mills, DiAnn (Center Point Large Print, 2019)
"There's a killer on the loose in Galveston, targeting law enforcement officials and using a fatal injection of snake venom to take them down. Authorities have reason to believe the Veneno gang is behind the hits, and FBI Agents Leah Riesel and Jon Colbert team up to track down those responsible. Their best lead is an eyewitness who identifies a young man dumping the third body on a church doorstep. But their suspect has gone into hiding, and those closest to him are reluctant to reveal anything that might help investigators find him. As Leah and Jon check connections among the victims and dig deeper into motives, they discover appearances may be deceiving. Someone is desperate to keep their secrets hidden, and Leah and Jon must face their greatest fears in order to stop the next fatal strike."--